Análisis y Reconfiguración de la Red de Media Tensión del Campus Matriz de la Universidad Nacional de Loja para la Integración de Generación Distribuida - Cabrera Villalta, Juan Carlos (2025)
This study analyzes the medium-voltage network of the main campus of the Universi- dad Nacional de Loja to propose a reconfiguration that enables the integration of distributed generation and ensure an efficient and safe distribution of electrical energy, ensuring the proper functioning of the system and reducing the affected area in the event of a failure at any point in the network, in compliance with the current national technical regulations. For this purpose, a detailed survey of the existing electrical infrastructure was conducted, followed by a diagnostic assessment of its current state. Subsequently, a new network topology was proposed, consi- dering the pre-established distributed generation injection points, guaranteeing the capacity to operate in isolated mode when necessary. To validate the proposal, simulations were performed using specialized software under two scenarios: one based on the campus’s current energy de- mand and another incorporating a 15-year demand projection, assuming an annual growth rate of 3%. The total power contribution from distributed generation systems was determined accor- ding to the specifications of the photovoltaic arrays proposed by the Electricity research team, accounting for an annual degradation rate of 1% in photovoltaic module efficiency. Finally, based on the analysis, the study identified the optimal common coupling point for the campus network to maintain stable operation when connected to the Cajanuma feeder. Additionally, an investment cost estimation was conducted for implementing the proposed reconfiguration.